Autoubiquitylation of the V(D)J recombinase protein RAG1 - Jones, Jessica M. (National Academy of Sciences, 2003)
V(D)J recombination, the rearrangement of gene segments to assemble Ig and T cell receptor coding regions, is vital to B and T lymphocyte development. Here, we demonstrate that the V(D)J recombinase protein RAG1 undergoes ubiquitylation in cells. In vitro, the RING finger domain of RAG1 acts as a ubiquitin ligase that mediates its own ubiquitylation at a highly conserved K residue in the RAG1 amino-terminal region. Ubiquitylation is best supported by a specific ubiquitin-conjugating enzyme, UbcH3/CDC34, and requires an intact RAG1 RING finger motif. Disruption of the RING finger and certain RAG1 N-terminal truncations are associated with immunodeficiency in human patients, suggesting that RAG1's ubiquitin ligase is required for its biological role in lymphocyte development.